Q: Can you Simplify -9 - 6x 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

6x + 9 + 2x = 8x + 9

7x + 7 + 6x - 9 = 13x - 2

-9

6x - 9 - x = 6Combine like terms on the left side:5x - 9 = 6Add 9 to each side:5x = 15Divide each side by 5:x = 3By the time you simplify it, you've solved it.

If that's 6x + 10, that factors to 2(3x + 5)

12x^2+10

6x^2

6x - 9 = 21 6x = 21 + 9 6x = 28 x = 28/6 Reduce to: x = 14/3

1+6x+6x+8 1+ 12x +8 12x + 9 = 21 + x

6x-2y

12

Following the correct order of operations, 8x + (1)(121) - (x/6x)(9)-x=8x+121-1.5-x=7x+119.5